Behaviour and repair of carpentry connections – Rotational behaviour of the rafter and tie beam connection in timber roof structures - Palma, P. (2012)
An extensive experimental campaign on structural carpentry connections, namely the rafter and tie beam connection, was conducted to assess their rotational behaviour and the effectiveness of some common repair and reinforcement techniques. The mechanical behaviour was appraised for different geometries, metal fastening devices and moisture content of timber. After the mechanical tests, some of the connections were repaired and tested again, which allowed comparing the performance of the original and the repaired connections. The compressive internal force in the rafter influences the connection’s behaviour, being crucial in maintaining the integrity of some of these carpentry joints. This aspect required a complex test apparatus and the design of specific equipment to simultaneously apply the compression force and the rotations in the rafter specimen. The experimental results show that some configurations exhibit enough rotation stiffness and load bearing capacity to be accounted for when appraising the roof structures they belong to, enhancing the common assumption of hinged joints. The connection’s behaviour is different when opening or closing the skew angle. Each connection typology exhibits specific load bearing mechanisms which dictate different performances and failure modes, which should be considered when devising a repair.